Socioeconomic and psychobehavioral aspects of active community elderly women during the SARS-CoV-2 pandemic (Research, Society and Development, 2022)
Older adults were significantly affected by the Covid-19 pandemic, both due to high mortality and social distancing to contain the spread of the virus. It is necessary to investigate the effects of this isolation in this population, subject to the physical, social and psychological changes of aging. Due to the period of restarting activities outside home and the impact of physical activity on quality of life, the objective was to describe the social, economic, cognitive and physical activity level of elderly women participating in community health programs after the period of isolation. Cross-sectional study from December 2021 to June 2022 in Goiânia-GO with 44 elderly women participating in community health programs that promote physical activity. Questionnaires that assessed general health status, socioeconomic (Brazil Old Age Schedule) and cognitive (Six-item Cognitive Impairment Test) aspects were applied. There was a reduced level of physical activity and the presence of a economically vulnerable population, with good performance in social relationships and expected cognitive performance for their age, directly influenced by the diagnosis of Covid-19, a possible risk factor. Health programs guarantee the population's access to primary care, but it is suggested that they promote strategies to encourage the practice of physical activity and social interaction. Elderly women made an important financial and affective contribution to the family. The risk for dementia represented an important variable when considering the diagnosis of Covid-19. It is suggested that further studies improve the analysis of physical activity as a protective factor for these variables.